Juridic Analysis Of An Old Village Overland Management Right (HPL) BP Batam (Research Study At Directorate Of The Batam Corporation Management Agency) - Mulyo Hadi; Lagat Parroha Patar Siadari; Erniyanti Erniyanti; Soerya Respationo (LITERACY : International Scientific Journals of Social, Education, Humanities, 2023)
The study considers the status of the old village on the island of Batam over land management rights (HP l) bp batam), while its people have long inhabited even the land of generations. Thus giving status to the old village on the island of Batam was a protection to the people who settled in the old village. The study employs a sociological juxtological approach, which is approached through current legal research and links with known facts in society, using a descriptive-analytic method with a qualitative approach. There was a conflict of authority between BP Batam and the municipality of the old village administration, BP Batam considered the old village to be a part of management rights, and the Batam City considered the old village to be a tribal land because its adb people had first occupied the region before the management of the land and therefore required a certain legal certainty on the island of batam. This study shows that with the status of the old village on Batam island, there are expected to be measures or policies on the settlement of the old village status in Batam city, both from the mayor and from the establishment of the old village and from the Batam free port as the management authority of the Batam city, the existence of the old village and its residents in order to be sure The law.